SURYA, TRI HITA KARANA DAN ADAPTASI TRANSISI ENERGI DI PURA BALI - Andi Nurul Mutmainnah; Arlin Adam; Syamsu A Kamaruddin; Ahmadin (Program Studi Sejarah Peradaban Islam, 2026)
The transition to renewable energy has largely been approached from a technical and policy-oriented perspective, while the social, symbolic, and religious dimensions remain underexplored. This study examines the acceptance of solar energy technology in Balinese temples in Legian, Bali, by analyzing the meaning of energy in Tri Hita Karana and the symbolism of Surya in Balinese Hindu cosmology. The study also investigates how religious habitus and symbolic capital shape the technology's legitimacy and identifies barriers related to economic capital and technical capacity. This research employed a qualitative case study design, employing in-depth interviews, participant observation, and document analysis involving temple caretakers, devotees, and village authorities. The findings indicate that solar technology is not perceived as something foreign, but as an extension of the cosmic energy associated with Surya. Its integration into temple spaces involves cultural negotiations regarding sacred space, ritual practices, and temple aesthetics. The technology's legitimacy is generated through religious practices and symbolic authority within the religious sphere. However, its implementation remains constrained by limited economic resources and technical capacity rather than cultural resistance. Theoretically, this study extends Bourdieu's framework by showing that technology adoption is the result of the interaction between habitus, symbolic capital, and economic capital in a socio-religious field.